SOSIALISASI PENTINGNYA BELAJAR BAHASA INGGRIS DALAM MENUMBUHKAN SEMANGAT BELAJAR SANTRI DAYAH INSAN QURANI ACEH BESAR - Hasni, Jusnaini; Devilishanti, Tio; Makmun, Abu Hassan; Yuliana, Desi; Hartini, Hartini; Suhendra, Noval; Hatmawan, Aglis Andhita; Rahma, Endah Anisa (Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2023)
English subject is one of important subjects in Indonesian national curriculum, including the boarding school curriculum. As in boarding school curriculum, the students are obligated to speak in foreign language (English or Arabic) in their daily routine. Because Islamic boarding school curriculums are mostly written and spoken in Arabic, sometimes the students feel unwillingly to study English. The purpose of this study is to improve the students’ interest in learning English in Insan Qurani Islamic boarding school. This activity is held by giving the material and giving the examples of using English and its importance in daily life. The result of this activity shows the improvement of students’ interest in learning English. It can be seen from their enthusiasm and participate during the activity and also reading the text asked by facilitator